The Christian Message as Vision and Mission : Philosophical Considerations of its Significance. - Sia, Santiago (Cambridge Scholars Publishing, 2017)
With all the messages that come our way through social media and in sophisticated gadgets, does the Christian message of love, hope and redemption still have an importance and relevance? What does it have to offer to enable us to meet the various challenges which beset present-day living? Today there is an even greater and more urgent need to focus on it. After all, the Christian message is not merely information because it is also about a way of life. Neither is it simply an exhortation since it also presents a definite goal. This book provides some philosophical considerations which underpin.